Geographic priorities for research and development on dryland cereals and legumes - Hyman, Glenn G.; Barona, Elizabeth; Biradar, Chandrashekhar M.; Guevara, Edward D.; Dixon, John; Beebe, Stephen E.; Castaño, Silvia Elena; Alabi, Tunrayo; Gumma, Murali K.; Sivasankar, Shoba; Rivera, Ovidio; Espinosa, Herlin; et al. (International Center for Tropical Agriculture, 2016)
Dryland cereal and legume crops have often received less attention than maize, wheat and rice in terms of research and development priorities. But these crops are important globally because they serve populations living in poverty and particular socioeconomic and environmental niches. Compared to other crops, less is known about the global distribution of dryland cereal and legume crops and the conditions where they are grown. This research reports on an international effort to compile geographic information on cereal and legume crops and the conditions under which they are cultivated.. The study suggested that dryland cereal and legume crops should be given priority in 18 farming systems worldwide, representing 160 million ha. The priority regions include the drier areas of South Asia, West and East Africa, Middle East and North Africa, Central America and other parts of Asia. These regions are prone to drought and heat stress, among other biotic and abiotic constraints. They represent 60% of the global poor and malnourished and make up half of the global population.